The cutting power of preparation - Olivier Tercieux; Mark Voorneveld (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
In a strategic game, a curb set [Basu and Weibull, Econ. Letters 36 (1991) 141] is a product set of pure strategies containing all best responses ro every possible belief restricted to this set. Prep sets [Voorneveld, Games Econ. Behav. 48 (2004) 403] relax this condition by only requiring the presence of at least one best response to such a belief. The purpose of this paper is to provide economically interesting classes of games in which minimal prep sets give sharp predictions, whereas in relevant subclasses of these games, minimal curb sets have no cutting power whatsoever and simply consist of the entire strategy space. These classes include potential games, congestion games with player-specific payoffs, and supermodular games.
Keywords: C72; 330; curb sets; prep sets; potential games; congestion games; supermodular games; Theorie; Nichtkooperatives Spiel